Keripik Daun Mangrove dalam Upaya OptimalisasiPemanfaatan Tanaman Mangrove - Desi Ramadhani; Dina Siti Maisyaroh; Cahyani Setianingrum; Dwi Retnaningsih (PT.Mantaya Idea Batara, 2022)
Demak is an area heavily farmed with mangrove plants because part of its area is a coastal area. However, with the large number of mangrove plants in the area it has not been utilized much. Community service activities carried out from October 2021 to February 2022, we are trying to create new innovations to optimize the use of mangrove plants in the form of chips from mangrove leaves of the brayo type which we named